Correlation between visceral fat area and cardiac valve calcification in hemodialysis patients - Wang, Xiaoqi; Yuan, Dan; Shao, Feng; Zhou, Jingjing; Zhang, Xiao; Li, Zhongxin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the relationship between Visceral Fat Area (VFA) and cardiac valve calcification (CVC) in Maintenance Hemodialysis (MHD) patients.MethodsThis cross-sectional study included MHD patients enrolled at our hospital between July 2023 and February 2024. Body composition analysis was performed on recruited patients. According to echocardiography results, the participants were classified into 2 groups. We then compared their clinical characteristics and identified independent factors influencing CVC through multivariate logistic regression. The ROC curve was employed to assess the ability of influencing factors to predict CVC in MHD patients.ResultsThere are 154 MHD patients were recruited, including 76 with CVC and 78 without CVC. Significant differences were observed between CVC and non-CVC participants in age, the proportion of diabetic nephropathy, the proportion of diabetes mellitus, the levels of Hs-CRP, fasting blood glucose, blood phosphorus, iPTH, HDL-C and VFA (P < 0.05). Advanced age, diabetes, increased VFA and iPTH all have the ability to predict individuals with CVC in MHD patients based on Multivariate Logistic regression. ROC curve indicated that VFA could accurately identify individuals with CVC among MHD patients (AUC = 0.713). When age, diabetes, iPTH, and VFA were combined for predicting CVC, the AUC was 0.776 (P < 0.01), which was greater than any single indicator.ConclusionsFor MHD patients, increased VFA may serve as a potential marker for detecting CVC and can assist in clinical decision-making.